2016
DOI: 10.2147/opth.s120158
|View full text |Cite
|
Sign up to set email alerts
|

Tear lipid layer thickness with eye drops in meibomian gland dysfunction

Abstract: PurposeThe aim of this study was to evaluate the efficacy of a lipid containing emollient eye drop, Soothe XP, which was reformulated in 2014 with a more stable preservative and buffer system, compared to a control, non-emollient, eye drop (Systane Ultra) in improving lipid layer thickness (LLT) in subjects with dry eye due to meibomian gland dysfunction (MGD).Patients and methodsThis prospective single-center, open-label, cross-over, examiner masked-study enrolled subjects aged 30–75 years with lipid-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 14 publications
2
31
0
2
Order By: Relevance
“…Sample size calculation was powered for a specified change in LLT using a different device to that used in this study (Stroboscopic Video Colour Microscope (SVCM) vs LipiView II). Although both instruments use interferometric methods to measure LLT, the areas of the tear film evaluated differ between these two instruments: the SVCM images a circular area of 6 mm diameter, 15 whereas the LipiView images the inferior region of the tear film. 30 Therefore, this study may not have been appropriately powered to detect change in LLT.…”
Section: Clinical Sciencementioning
confidence: 99%
“…Sample size calculation was powered for a specified change in LLT using a different device to that used in this study (Stroboscopic Video Colour Microscope (SVCM) vs LipiView II). Although both instruments use interferometric methods to measure LLT, the areas of the tear film evaluated differ between these two instruments: the SVCM images a circular area of 6 mm diameter, 15 whereas the LipiView images the inferior region of the tear film. 30 Therefore, this study may not have been appropriately powered to detect change in LLT.…”
Section: Clinical Sciencementioning
confidence: 99%
“…The inferior field is similar to that used in previous studies. 7,8 Assessment of the central and superior areas of the cornea is appropriate as the tear film moves on the ocular surface during a blink. 13 For this study, 900 frames were collected over 40 seconds for each measurement session.…”
Section: Outcome Measures and Assessmentsmentioning
confidence: 99%
“…Studies have found that eye drops containing emollients can help to increase the lipid layer thickness (LLT) of the tear film in the short term. 7,8 Omega-3 fatty acids can be found in the normal tear film, with profiles of these lipids correlating with dry eye severity. 9 While previous studies have found conflicting results as to whether dietary supplementation with omega-3 fatty acids can aid in the treatment of dry eye, 10,11 no studies to date have been done to determine if an eye drop containing omega-3 fatty acids can thicken the lipid layer of the tears.…”
Section: Introductionmentioning
confidence: 99%
“…ISSN 1816-5095 (print); ISSN 2500-0845 (online) doi: 10.18008/1816-5095-2016-4-235-240 Методы скрининговой диагностики дисфункции мейбомиевых желез 1 Федеральное государственное бюджетное образовательное учреждение дополнительного профессионального образования «Институт повышения квалификации Федерального медико-биологического агентства», ул. Гамалеи, 15, Москва, 123098, Российская Федерация Актуальность своевременной диагностики дисфункции мейбомиевых желез (ДМЖ) возрастает с каждым днем.…”
unclassified
“…В первую очередь, это связано с тем, что в настоя-щее время изменились представления о распространен-ности данной патологии, которая по разным данным составляет от 40 до 71% населения в различных воз-растных группах [1,2,3]. Кроме того, данные научных исследований, направленных на изучение дисфункции мейбомиевых желез, свидетельствуют о том, что на их функциональное состояние оказывают влияние не толь-ко системные факторы, такие как дефицит андрогенов, менопауза, старение, синдром Шегрена, повышенное со-держание холестерина, псориаз, атопия, розовые угри, гипертония и доброкачественная гиперплазия простаты.…”
unclassified